Characterization of the EGFR interactome reveals associated protein complex networks and intracellular receptor dynamics. Issue 21 (1st October 2013) - Foerster, Sarah; Kacprowski, Tim; Dhople, Vishnu Mukund; Hammer, Elke; Herzog, Susann; Saafan, Hisham; Bien‐Möller, Sandra; Albrecht, Mario; Völker, Uwe; Ritter, Christoph A.
<x xml:space="preserve">Abstract</x> Growth factor receptor mediated signaling is meanwhile recognized as a complex signaling network, which is initiated by recruiting specific patterns of adaptor proteins to the intracellular domain of epidermal growth factor receptor (EGFR). Approaches to globally identify EGFR‐binding proteins are required to elucidate this network. We affinity‐purified EGFR with its interacting proteins by coprecipitation from lysates of A431 cells. A total of 183 proteins were repeatedly detected in high‐resolution MS measurements. For 15 of these, direct interactions with EGFR were listed in the iRefIndex interaction database, including Grb2, shc‐1, SOS1 and 2, STAT 1 and 3, AP2, UBS3B, and ERRFI. The newly developed Cytoscape plugin ModuleGraph allowed retrieving and visualizing 93 well‐described protein complexes that contained at least one of the proteins found to interact with EGFR in our experiments. Abundances of 14 proteins were modulated more than twofold upon EGFR activation whereof clathrin‐associated adaptor complex AP‐2 showed 4.6‐fold enrichment. These proteins were further annotated with different cellular compartments. Finally, interactions of AP‐2 proteins and the newly discovered interaction of CIP2A could be verified. In conclusion, a powerful technique is presented that allowed identification and quantitative assessment of the EGFR interactome to provide further insight into EGFR signaling.